The Correlation between Microalbuminuria and Thyroid Nodules in Type 2 Diabetic Mellitus - Can Cao; Zhao-Li Cui; Juan Miao; Jing-Xin Zhou; Xiao-Nan Wang; Jian Jin (International Journal of Endocrinology)
Objective. To investigate the correlation between thyroid nodules and microalbuminuria in type 2 diabetic mellitus. Methods. A total of 270 patients with type 2 diabetes at Tongzhou Branch of Dongzhimen Hospital were enrolled in this retrospective study. Data were collected from the inpatient electronic files between January 2018 and January 2020. The laboratory indexes of the two groups (thyroid nodule group with 172 cases and control group including 98 cases without thyroid nodules) were statistically analyzed by binomial logistic regression analysis and Spearman correlation analysis. Results. The proportion of microalbuminuria (MAU) in the thyroid nodule group was larger than that in the control group. Age, serum TT4, and FT4 in the thyroid nodule group were significantly higher compared with the control group. The binary logistic regression analysis indicated that age, sex, FT4, and MAU were the risk factors for thyroid nodule in T2DM patients. Spearman correlation analysis showed that the thyroid nodule was significantly positively correlated with MAU, age, FT4, and TT4. Conclusions. MAU might be an independent risk factor for thyroid nodule in type 2 diabetic mellitus.